Building Confidence in the Justice System Through Civics, Civility, and Collaboration - Nelson, Adrienne C (The Judges' journal, 2023)
The federal level contains district courts, circuit courts, and the U.S. Supreme Court, and each state contains its own trial courts, courts of appeals, and supreme court (though the precise names of these courts may vary from state to state). Or, as another example, when a federal district court issues a controversial opinion, it may engender concern precisely because the public does not know that those decisions are subject to review by, at least, one other court. The essence of a lawyer's role is to "agree to disagree.'" When motions are filed and oral arguments are heard, or when an attorney objects to the admission of evidence, each attorney believes their position is correct. The average American may not understand the difference between the federal court system and the state court systems, but an attorney does. Constitutional law is a foundational course in many law schools across the United States-from a future lawyer's first year of law school, they receive an in-depth civics education that many Americans do not have access to.